Experimental investigation of self-excited combustion instabilities with injection coupling in a cryogenic rocket combustor. (October 2018) - Armbruster, Wolfgang; Hardi, Justin S.; Suslov, Dmitry; Oschwald, Michael
Abstract: The cryogenic LOX/H2 multi-injector research combustor "BKD" allows the investigation of high-frequency combustion instabilities under realistic conditions. Two different types of self-excited instabilities were observed. For one instability the underlying coupling mechanism was already identified as LOX injection-driven. The second type of combustion instability was experienced for different operating conditions and is characterized by higher amplitudes, more than 75% of the static chamber pressure. Analysis of the pressure data showed that amplitude and frequency of the acoustic field vary strongly over time, which complicates interpretation of the coupling mechanism. A normalization of the shifting frequency shows that the increase of oscillation frequency depends on transverse acoustic velocity. This is an effect that has also been noticed in other experiments and simulations and is explained by improved mixing leading to a reduced length of the combustion zone. This observation suggests that during the large amplitude pressure oscillations the mode shape remains a first tangential (1T) mode with shifting frequency. By using highly resolved information of the acoustic field in the time domain, both from the combustion chamber and the injector volumes, in combination with acoustic modelling of the injector elements, insights into the coupling mechanism could be gained. For periods of lower amplitudes the pressure oscillations are LOX injector-driven, similar to the first type of instability. With increasing amplitude also the frequency of the unstable mode increases and shifts into a region, where interaction with the hydrogen injector 1L mode becomes possible. Highlights: Combustion instability frequency is increasing with growing instability amplitudes. Frequency shift seems to be result of flame length reduction due to enhanced mixing. Varying frequency leads to a triple-coupling mechanism. At low frequency there is injection-coupling with liquid oxygen injector posts. Increased frequency allows interaction with 1L mode of fuel injectors.